Effect Of Supplementation Of Chromium Nanoparticles On Egg Weight And Egg Quality Characteristics In Layers - Malathi, V.; Jayanaik; Gowda , N.K.S. (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
A study was conducted to investigate the effect of supplementation of different levels of Chromium nanoparticles (NanoCr) in layers. 360 brown layers of 28 weeks age were randomly allocated to five treatment groups (supplemented with 0, 50, 100, 200 and 400 ppb NanoCr). At 32, 36 and 40 weeks age, eggs were collected to assess the egg weight, yolk, albumen, shell per cent and shell thickness, Haugh unit and egg indices. Egg weight linearly increased at all ages with NanoCr. Albumen per cent significantly increased and yolk and shell per cent significantly decreased (p
Keywords: Chromium; Nanoparticles; Egg weight; Egg quality; Layers